2020
DOI: 10.1167/iovs.61.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Potentiates Orbital Tissues for Inflammation Through NF-κB and MCP-1

Abstract: The orbit displays unique vulnerability to inflammatory conditions. The most prevalent of these conditions, thyroid eye disease (TED), occurs in up to 50% of patients with Graves' disease (GD). Whereas the pathology of both TED and GD is driven by autoantibodies, it is unclear why symptoms manifest specifically in the orbit. METHODS. We performed retinoic acid treatment on both normal and TED patient-derived orbital fibroblasts (OFs) followed by mRNA and protein isolation, quantitative realtime polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Apparently, this study showed that TNF-α inhibition lowered NF-kB expression and MCP-1 was reduced, following the treatment with a protein-rich-cake (10%PMEC) by a factor of 4. Consistent with our finding, Park et al [81] and Unsworth et al [82] reported that MCP-1 activation induced NF-kB expression, while NF-kB inhibition was reported to prevent TNF-α and MCP-1 inflammatory responses in humans. Thus, it is possible that reduced MCP-1 activation by inhibiting NF-kB with down-regulation of TNF-α in rats treated with protein-rich-cake (10% PMEC) by a factor of 4 could account for the delayed progression of IMED.…”
Section: Discussionsupporting
confidence: 93%
“…Apparently, this study showed that TNF-α inhibition lowered NF-kB expression and MCP-1 was reduced, following the treatment with a protein-rich-cake (10%PMEC) by a factor of 4. Consistent with our finding, Park et al [81] and Unsworth et al [82] reported that MCP-1 activation induced NF-kB expression, while NF-kB inhibition was reported to prevent TNF-α and MCP-1 inflammatory responses in humans. Thus, it is possible that reduced MCP-1 activation by inhibiting NF-kB with down-regulation of TNF-α in rats treated with protein-rich-cake (10% PMEC) by a factor of 4 could account for the delayed progression of IMED.…”
Section: Discussionsupporting
confidence: 93%
“…A recent article by Unsworth et al [26 ▪▪ ] argues that retinoid byproducts of the visual chromophore, 11-cis-retinal [27], diffuse across the sclera, accumulate in orbital fatty tissue, and cause de novo synthesis and secretion of MCP-1 (also known as CCL2), an important chemoattractant in orbital inflammatory conditions [28–32]. Indeed, it has long been known that orbital fat is enriched in retinoids [33], and Unsworth et al [26 ▪▪ ] take it a step further by demonstrating that retinoids can diffuse across the sclera in an in-vitro model.…”
Section: Targeting the Orbit For Inflammationmentioning
confidence: 99%
“…A recent article by Unsworth et al [26 ▪▪ ] argues that retinoid byproducts of the visual chromophore, 11-cis-retinal [27], diffuse across the sclera, accumulate in orbital fatty tissue, and cause de novo synthesis and secretion of MCP-1 (also known as CCL2), an important chemoattractant in orbital inflammatory conditions [28–32]. Indeed, it has long been known that orbital fat is enriched in retinoids [33], and Unsworth et al [26 ▪▪ ] take it a step further by demonstrating that retinoids can diffuse across the sclera in an in-vitro model. Retinoids that accumulate in orbital tissues outside the eye will be henceforth referred to as ‘tissue retinoids.’ The mechanism of action by retinoids involves the role of retinoids as regulators of transcription through binding to retinoic acid receptors (RAR) and retinoid X receptor (RXR) [34–40].…”
Section: Targeting the Orbit For Inflammationmentioning
confidence: 99%
See 2 more Smart Citations